High capacity LifePo 4 battery model with consideration of nonlinear capacity effects - Low, Wen Yao (IEEE, 2012)
Lithium Ferro Phosphates (LiFePO 4) batteries have high potential to be widely employed in the future due to its stability on chemical and thermal characteristics. Therefore, an accurate battery model of high capacity LiFePO 4 battery is important for a circuit designer to handle and optimize battery usage. However, nonlinear capacity effects of the battery are usually not been considered. The ignorance of nonlinear capacity effects cause the existing battery models unable to perform accurately. In this paper, nonlinear capacity effects of high capacity battery are studied. A new battery model is developed with consideration of nonlinear capacity effects. Developed battery model is validated from the experimental results. Comparison between experimental and simulation results shows that the developed model is capable to capture nonlinear capacity effects of the high capacity battery.